Geospatial-Based Information System for Visitor Management in the Baduy Region - Asyifa Catur Rahmadini; Priya Tharsini; Yerik Afrianto Singgalen (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research presents the development of a Geospatial-Based Information System prototype for visitor management in Indonesia's culturally sensitive Baduy indigenous region. The study addresses the critical challenge of balancing cultural preservation with sustainable tourism development through an innovative technological framework that respects indigenous sovereignty. Utilizing Rapid Application Development (RAD) methodology, the research integrates traditional knowledge systems with modern geospatial technologies to create a governance tool that enhances rather than displaces traditional decision-making structures. The prototype system architecture incorporates permit management workflows, GPS-enabled check-in protocols, and spatial monitoring capabilities that enable Jaro authorities to regulate visitor access, monitor distribution patterns, and enforce culturally appropriate boundaries. Black box testing validated the prototype's functionality across multiple operational scenarios, confirming its feasibility as a protective mechanism against unregulated tourism activities. This methodological approach to cross-cultural information system design establishes a foundational framework demonstrating how thoughtfully implemented geospatial technologies amplify Indigenous governance capabilities while creating sustainable economic opportunities aligned with traditional values and cultural preservation imperatives. The research contributes significantly to the discourse on Indigenous digital sovereignty and culturally appropriate technological interventions in heritage management.